Effect of Different Cryopreservation Regimens on Capability of Placenta Suspension to Manifest an Immune-Correcting Activity When Treating Adjuvant Arthritis in Mice - Rassokha, I. V.; Goltsev, A. N.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2004)
Therapeutic potential of placenta suspension (PS), cryopreserved under different regimens, in the model of adjuvant arthritis (AA) was investigated in mice. We have developed the method of PS cryopreservation, enabling a maximum preservation of natural heterogeneity in placenta cell populations and their correcting effect in respect of clinical and laboratory indices and recovery of structural and functional organisation of central and peripheric organs of lymphohemopoietic complex (LHPC) under autoimmune pathology development.